Analysis of Higher Order Thinking Skills Components on The Contents of Physics for Class X Semester II High School in West Sumatera - Abdul Azis; Yenni Darvina; - Gusnedi; Silvi Yulia Sari (PILLAR OF PHYSICS EDUCATION, 2021)
One of the essences of curriculum implementation in 2013 is the application of high-level thinking skills-rotating learning ( Higher Order Thingking Sklills,HOTS). HOTS-oriented learning requires students to carry out active learning. Therefore, the teacher must be able to create active learning by presenting one of the teaching materials in the form of Student Worksheets (LKS). The results of observations show that the LKS used in public high schools in North Sumatra is still diverse, starting from the LKS made by the subject teachers and issued by the publisher. All of these LKS have also not been identified whether they already contain HOTS components in them. therefore, a component analysis research was conducted higher Order thinking skills (HOTS) on the material presentation Physics worksheets class X semester II at SMAN throughout West Sumatra.This research is a descriptive study with a qualitative approach. The population of data in this study were all worksheets for high school physics students of class X semester II used by 34 public high schools in West Sumatra. The sample in this study is the highest number of SMA class X semester II physics worksheets used in schools published by three different publishers and two worksheets made by physics subject teachers.The research data were taken using the analysis instrument of LKS offerings and data collection techniques through documentation studies.Based on the research that has been carried out, it is found that the percentage of availability of HOT indicators in the form of decision making, critical thinking and creative thinking in each worksheet is as follows. LKS F X/II RZ-GR percentage of indicator availability LKS / IIX percentage availability of HOTS indicators respectively, namely, 23,34% ; 0,%; 35,52%; 22,88%. LKS D X/II RC-IP, 44,66%;25,74%; 44,42%;40,04%. LKS F X/II BK-VP , 16,86%; 8,58% ; 28,86%; 2,86 %.LKS F X/II G I, 21,66%; 2,86%;35,52%; 5,72% and LKS F X/II GII, 28,31%; 11,44%; 33,3% ;17,16%. From the entire LKS F X/II RC-IP Has the highest percentage indicator. From this data, it can be concluded that the percentage of availability of HOTS indicators in the presentation of the contents of the Class X Semester II Physics Worksheets at Senior High Schools throughout West Sumatra is still low, with the category not yet facilitating.Keywords : Analysis, worksheet, High Order Thinking Skills (HOTS).